Determinants of low birth weight deliveries at five referral hospitals in Western Area Urban district, Sierra Leone - David Kabba Kargbo; Kofi Nyarko; Samuel Sackey; Adolphina Addo-Lartey; Ernest Kenu; Francis Anto (BMC, 2021)
Abstract Background Low birth weight (LBW) contributes significantly to infant and child mortality. Each year, about 20 1million deliveries are LBW with 96.5% occurring in developing countries. Whiles the incidence of LBW is reducing in other districts of Sierra Leone, it has been reported to be increasing in the Western Area Urban district. Determining the risk factors in a specific geographic area is important for identifying mothers at risk and thereby for planning and taking appropriate action. The current study sought to identify factors associated with LBW deliveries in the Western Area Urban district of Sierra Leone. Methods A hospital-based unmatched 1:2 case-control study was conducted among mothers who delivered live singleton babies from November, 2019 to February, 2020 in five referral health facilities. Mothers were conveniently sampled and sequentially enrolled into the study after delivery. Their antenatal care cards were reviewed and a pre-tested questionnaire administered to the mothers. Data analysis was done using Stata 15.0 and association between maternal socio-demographic, socio-economic, obstetric and lifestyle factors and LBW assessed using bivariable and multivariable logistic regression analyses. Results A total of 438 mothers (146 cases and 292 controls), mean age: 24.2 (±5.8) and 26.1 (±5.5) years for cases and controls respectively participated in the study. Multivariable analysis revealed that being unemployed (AoR = 2.52, 95% CI 1.16-5.49, p = 0.020), having anaemia during pregnancy (AoR = 3.88, 95% CI 1.90-7.90, p <  0.001), having less than 2 years inter-pregnancy interval (AoR = 2.53, 95% CI 1.11-5.73, p = 0.026), and smoking cigarettes during pregnancy (AoR = 4.36, 95% CI 1.94-9.80, p <  0.001) were significantly associated with having LBW babies. Conclusion Factors associated with LBW identified were unemployment, anaemia during pregnancy, < 2 years inter-pregnancy interval and cigarette smoking during pregnancy. Health care providers should screen and sensitize mothers on the risk factors of LBW during antenatal sessions.